Work/family programs and the employment relationship. - Osterman, Paul (Administrative Science Quarterly, 1995)
Using data from a representative sample of American private-sector establishments, this paper explains variation across firms in the implementation of work/family programs by examining how these are related to the employment strategy of organizations. The central hypothesis is that firms seeking to implement so-called high-performance or high-commitment work systems, incorporating employee involvement and quality programs, are more likely to adopt work/family programs as part of an effort to build up the level of workforce commitment to the enterprise. This hypothesis is tested, controlling for two other broad hypothesized effects: (1) that adoption of work/family programs is linked to the demand for them arising either from workforce problems such as absenteeism and turnover or from pressure from the labor force; and (2) that adoption is linked to whether employers already have in place elements of well-developed internal labor markets such as job ladders and human resource departments. Results show considerable support for the link between work/family programs and the use of high-commitment work systems. Reprinted by permission of the publisher.